Organ-on-a-chip approaches for panvascular device evaluation: insights from the FLOW framework - Guanzhao Zhang; Shuting Chang; Yunfan Pan; Xingyu Jiang (Science Bulletin, 2026)

The co-assembled hesperidin-emodin nanospindles for synergistic enhancement of regenerative repair in MRSA-infected incisions - Li Chang; Shuting Xie; Pengxiang Xu; Zhoubing Shan; Aidi Tong; Mingbao Luan; Chunyi Tong; Bin Liu (Chemical Engineering Journal, 2026)

Paleoglacial coverage and paleoclimatic reconstruction of MIS 3b and the gLGM in the Turgen–Asgat Catchment, Altai Mountains - Chang Liu; Liang Liu; Yijie Zhai; Shuting Han; Zheng Yang; Wei Zhang (Journal of Earth System Science, 2026)

Boosting hydrogen evolution activity of porous NiCo nitrides via modulating d-band center in alkaline seawater electrocatalysis - Tingting Wu; Xiaojing Li; Yifan Li; Shuting Zhang; Wenjiao Chang; Jingqi Chi; Lei Wang (Chemical Engineering Journal, 2025)

Effects of Clitocybe squamulosa polysaccharides on the intestinal microenvironment and microbiome of cyclophosphamide-induced mice - Xueran Geng; Dongdong Guo; Guangliang Ge; Zehui Li; Shuting Hou; Tergun Bau; Sitong Yao; Lijing Xu; Yanfen Cheng; Ludan Hou; Junlong Meng; Mingchang Chang (Food Bioscience, 2025)

Antioxidant and antimicrobial sodium alginate/sodium carboxymethyl cellulose films loaded with self-assembled hesperidin nanorods for fruits preservation - Zexin Gao; Shuting Xie; Li Chang; Huijuan Tang; Zhimin Sun; Yong Deng; Yinqi Hu; Ying Xu; Mingbao Luan (Food Chemistry, 2025)

Regulating surface band structure of anisotropic SrTiO3 via ultrathin TiO2 layer to promote spatial charge separation - Shuting Zhang; Honghuo Wang; Tingting Wu; Wenjiao Chang; Yifan Li; Junying Wang; Yongqiang Yang; Lei Wang (Chemical Engineering Journal, 2025)

Adsorptive removal of radioactive technetium by nanomaterials - Jingyang Sun; Xiaolian Yi; Chang Yuan; Wangming Zhu; Mingjia Liao; Yiyang Ye; Dameng Liu; Huan Liu; Shuting Zhuang (Reviews in Environmental Science and Bio/Technology, 2025)

Structure–activity relationship of a dual-function amine-based electrolyte for integrated CO2 capture and electrochemical conversion - Qiang Li; Tongxin Qu; Shuting Tan; Teng Wang; Yuhang Ding; Chang Wang; Junying Zhang; Zhuo Xiong; Yongchun Zhao (Chemical Engineering Journal, 2024)

Blood-based biomarkers for Alzheimer’s disease: a multicenter-based cross-sectional and longitudinal study in China - Feng Gao; Linbin Dai; Qiong Wang; Chang Liu; Kexue Deng; Zhaozhao Cheng; Xinyi Lv; Yan Wu; Ziyi Zhang; Qingqing Tao; Jing Yuan; Shiping Li; et al. (Science Bulletin, 2023)

A review of advanced oxidation process towards organic pollutants and its potential application in fracturing flowback fluid - Xing Li; Yang Bai; Xian Shi; Shuang Chang; Shuting Tian; Meiming He; Na Su; Pingya Luo; Wanfen Pu; Zhicheng Pan (Environmental Science and Pollution Research, 2023)

Airborne polystyrene microplastics and nanoplastics induce nasal and lung microbial dysbiosis in mice - Hua Zha; Jiafeng Xia; Shengjie Li; Jiawen Lv; Aoxiang Zhuge; Ruiqi Tang; Shuting Wang; Kaiceng Wang; Kevin Chang; Lanjuan Li (Chemosphere, 2023)

Investigating multi-way impacts of transportation on human footprint: Evidence from China - Shuting Chen; Yurui Li; Zhi Lu; Rui Li; Genying Chang (Environmental Impact Assessment Review, 2023)

Role of clouds in accelerating cold‐season warming during 2000–2015 over the Tibetan Plateau - Shan Hua; Yuzhi Liu; Rui Jia; Shuting Chang; Chuqiao Wu; Qingzhe Zhu; Tianbin Shao; Bing Wang (International Journal of Climatology, 2018)
With the global warming slowdown in the twenty‐first century, a huge discrepancy in regional climate warming has been identified over the main region of the Tibetan Plateau (TP). Compared with the +0.04 °C/decade warming from 1961 to 1999, the warming greatly accelerated for the period 2000–2015 at a rate of +0.30 °C/decade. During the same period, warming in the cold season (November to March) was more pronounced than in the warm season (May to September) over the TP. The results also indicated that the middle‐level cloud (middle cloud) decreased (−0.359%/year), while the high‐level cloud (high cloud) increased (+0.241%/year) over almost all the TP during the cold season. Further analysis showed positive net cloud radiative forcing over the western TP from 2000–2015, that is, a heating effect of clouds, especially in the cold season. Combining the trends of the increase in high cloud and the decrease in middle cloud over most parts of the TP, the decreased albedo effect of middle cloud and the increased longwave greenhouse effect of high cloud may have partially contributed to the sustained warming, especially in the cold season from 2000 to 2015. Meanwhile, the results showed that the warming rate and cloud area fraction changes were significantly amplified with elevation. The analysis based on a model of Coupled Model Intercomparison Project Phase 5 shows that the decreased middle cloud plays more important role than the increased high cloud in modulating the enhanced warming over the TP, especially in the cold season.